The language of incarceration. Issue 1 (9th July 2020) - Cox, Alexandra
This brief think piece considers the uses of "people first" language in the context of incarceration, both from a historical and contemporary perspective, and offers some thoughts about the use of this language by prison researchers. It focuses on the uses of such language in the context of disability studies and rights, and the focus on language by activists working to challenge systemic racism and abuse in prison systems in the 1960s and 1970s. It makes an argument for prison researchers to work intentionally with their use of language in keeping with broader disciplinary concerns around meaning making in prisons.